Keynes and Economic Policy - Eltis, W.A. author. aut Link
XVIII, 473 p.
Keywords: A collection of papers on the relevance of Keynes' economic theory after 50 years. It covers a diversity of topics relating the theory to subjects varying from the effect of fiscal reflation upon employment, and the significance of public sector borrowing to the international dimension.